A Prova Paraná e o apagamento da literatura - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This dissertation studies the Prova Paraná, a large-scale assessment promoted by the Paraná State Department of Education, whose reference matrix does not include knowledge of literature. The specific objects of this dissertation are three booklets of the Prova Paraná, the third edition of 2022 referring to the first year of high school and the first edition of 2023 referring to the first and second year of high school, totaling the analysis of fifteen questions. As a basis, we have studies by CECHINEL (2019), COMPAGNON (2009), COSSOM (2021), FELIPPE (2023), IPIRANGA (2019), SAVARIS (2022) among other authors. Also used for reflection are the official documents, Orientações Curriculares para o Ensino Médio – OCEM (2006) and the Base Nacional Comum Curricular – BNCC (2018). The general aim of this research is to reflect on the effects of omitting literature from the curriculum matrix of this assessment in Paraná. In view of this, the specific objectives are: to present the ways in which literature is considered in official documents – Curriculum Guidelines for Secondary Education and the National Common Curriculum Base; to analyze the content of questions and alternatives referring to literary texts related to the Portuguese Language curriculum component in the Paraná Test in selected editions; and to promote a study of educational proposals drawn up by specialists in the field of literature. Given this scenario, the aim is to answer what the implications are of excluding literature from the Paraná Test. Bibliographical and documentary research was used to develop this study, constituting a methodology of a qualitative nature.
Keywords: Avaliação de larga escala; Prova Paraná; Literatura; Base Nacional Comum Curricular; Ensino; Large-scale assessment; Paraná Test; Literature; National Common Core Curriculum; Teaching; CNPQ::LINGUISTICA, LETRAS E ARTES